Coworking: uma construção discursiva do trabalho em torno de mecanismos de poder biopolítico - Santos, Eliane Ferreira dos (2019)
This study examines how coworking can be understood as a discursive construction of work around mechanisms of biopolitcal power. We have observed few studies in the international literature that have proposed to articulate the mechanisms of biopolitical power (FOUCAULT, 2008b) with the field of work and organizations (FLEMING, 2012; 2014; MUNRO, 2012), such theme at the national level. The present research aims at identifying and analyzing the discourse on the coworking spaces that show a certain neoliberal ethos (HANNANN, 2009; MILLER e ROSE, 2012; ROSE, 2011) that imposes on the life of individuals, according to the precepts of a new governmental reason, of individual as company of self and human capital. To demonstrate how this process is constructed through documental analysis of three sources (Impact Hub coworking site, Brazilian Coworking Association and Exame Magazine) and discourse analysis. We adopta two aspects of the art of governing (MILLER e ROSE, 2012; ROSE 2011): the rationalities (related to the way of representing the object of analysis, making it knowable, calculate and manageable) and mechanisms (related to the aspects that shape, standardize and instrumentalize behavior, thinking, decisions and people’s aspirations). The analysis revelead, by means of discursive categories and formations, the subjective aspects intrinsic to the concept of coworking and to the construction of the “coworker” subject, an autonomous individual, an entrepreuner of himself, subject to a neoliberal ethos that palces his subjectivity at service of an economic rationality.